Aztreonam/avibactam effect on pharmacodynamic indices for mutant selection of Escherichia coli and Klebsiella pneumoniae harbouring serine- and New Delhi metallo-β-lactamases. (12th August 2021) - Feng, Kun; Jia, Nan; Zhu, Peijuan; Sy, Serubbabel; Liu, Yanfei; Dong, Dandan; Zhu, Shixing; Zhang, Jiayuan; Liu, Yuwei; Martins, Frederico S; Gong, Hugh; Lv, Zhihua; et al.
Abstract: Objectives: Ceftazidime/avibactam is not active against MBL-producing bacteria. Combining ceftazidime/avibactam or avibactam with aztreonam can counter the resistance of MBL-producing Enterobacterales. The aim of this study was to evaluate whether the addition of avibactam could reduce or close the mutant selection window (MSW) of aztreonam in Escherichia coli and Klebsiella pneumoniae harbouring MBLs; MSW is a pharmacodynamic (PD) parameter for the selection of emergent resistant mutants. Methods: In vitro susceptibility of 19 clinical isolates to ceftazidime/avibactam, aztreonam alone, and in co-administration (aztreonam/ceftazidime/avibactam and aztreonam/avibactam) was determined, as well as the mutant prevention concentration (MPC). The fraction of time within 24 h that the free drug concentration was within the MSW ( fT MSW ) and the fraction of time that the free drug concentration was above the MPC ( fT >MPC ) in both plasma and epithelial lining fluid (ELF) were determined from simulations of 10 000 profiles. The joint PTA was used to derive a joint cumulative fraction of response (CFR). Results: All isolates were resistant to ceftazidime/avibactam or aztreonam. Combining aztreonam and avibactam or ceftazidime/avibactam resulted in synergistic bactericidal activities against all isolates. Synergism was primarily due to the aztreonam/avibactam combination. For aztreonam/avibactam dosing regimens evaluated in clinical trials, fT >MPC values were >90% and >80%, whereas fT MSW measures were <10% and <20% in plasma and ELF, respectively. The CFR was 100% for aztreonam/avibactam against the collection of clinical isolates. Conclusions: Effective antimicrobial combination optimized the PD parameters measuring selection for emergent mutants by increasing fT >MPC and reducing fT MSW .